Association between surgery and increased survival in primary central nervous system lymphoma: a retrospective cohort study - Gangping Li; XinJiang Hou; Yuewen Fu; DongJie He; Di Zhang (Scientific Reports)
Abstract This study investigated the effect of surgery on the prognosis of patients with primary central nervous system lymphoma (PCNSL) using data from the surveillance, epidemiology, and end results (SEER) database. A cohort of 5932 patients was analyzed, with 1466 undergoing surgical intervention (780 subtotal resection (STR), 686 gross total resection (GTR)) and 4466 receiving no surgery or biopsy only. The median age of the study population was 61.5 years. The median survival was 24.0 months for STR, 30.0 months for GTR, and 18.0 months for non-surgical patients (P < 0.001). Multivariate Cox regression analyses showed that the adjusted hazard ratio (HR) for STR was 0.77 (95% CI 0.70–0.85, P < 0.001) for overall survival (OS) and 0.74 (95% CI 0.66–0.83, P < 0.001) for cancer-specific survival (CSS). For GTR, the adjusted HR was 0.73 (95% CI 0.65–0.80, P < 0.001) for OS and 0.73 (95% CI 0.65–0.82, P < 0.001) for CSS. These results remained robust even after subgroup analyses, sensitivity analyses and propensity score matching (PSM). No significant interactions were observed in any subgroup. These findings indicate that surgery may improve the survival of patients with PCNSL, though further research is needed to confirm these findings. A key limitation is the inability to stratify patients by performance status and lesion number, critical for assessing resective surgery suitability.